Genetic approach to select against embryo mortality caused by Enterococcus faecalis infection in laying hens. (11th August 2018) - Blanco, A E; Cavero, D; Icken, W; Voss, M; Schmutz, M; Preisinger, R; Sharifi, A R
Abstract: Selection to reduce susceptibility to Enterococcus faecalis infection in laying hens may contribute to the prevention of amyloid arthropathy since it is mainly induced by this bacterium. Therefore, the aim of the present study was to investigate the possibility to select more laying hens that are resistant against E. faecalis infection through the embryo lethality assay (ELA), which is proposed as an alternative model to replace the adult avian challenge assay. Ten-day-old embryos of 500 Lohmann Brown layers were inoculated into the allantoic cavity with an infectious dose of 2.5 colony-forming units (cfu)/mL of the avian E. faecalis strain K923/96 in 3 ELAs. The embryonic mortality rate (EMR) was determined by candling the eggs daily over a period of 4 d. The average EMR estimated during the 3 ELAs was 50% and the highest EMR occurred 3 to 4 d post inoculation. The estimated heritability for embryonic survivability to the infection was h 2 = 0.12–0.14, calculated with the logistic and probit link function, respectively, indicating that the selection of more laying hens that are resistant to E. faecalis infection is feasible. A highly negative genetic correlation was estimated between embryonic survivability and laying performance at the peak of lay (rg = –0.22) and at the end of the production (rg = –0.65), as well as with breaking strength (rg = –0.30 to –0.37). A positive correlation was found between egg weight and the embryonic survivability (rg = +0.16), and no genetic correlation was found with body weight and dynamic stiffness. Therefore, although it was demonstrated that it is possible to breed for E. faecalis resistance, special care should be taken to monitor and to take all traits and their genetic correlations into account in order to achieve a balanced genetic progress. Besides, the ELA does not require that the hens are exposed to pathogens thereby saving labor and cost. Therefore, it could be feasible that ELA be implemented in selection programs.